Enhancement effects of (R) and (S) enantiomers and the racemate of a model enhancer on permeation of theophylline through human skin - Vávrová, Katerina; Hrabálek, Alexandr; Dolezal, Pavel (Archives of dermatological research.., 2002)
The conformation of a permeation enhancer, given their mechanism of action, could influence its enhancing properties, since the stratum corneum components form essentially a chiral environment. The racemate and both enantiomers of 6-aminohexanoic acid 2-octylester as model enhancers with one chiral center were synthesized and their ability to enhance in vitro theophylline permeation through human skin was tested. The MTMT concept could not be applied in this study (the melting points of the substances were lower than 20 masculine C) and we observed no significant difference in enhancement ratios (ERs) of racemic 6-aminohexanoic acid 2-octylester and that of each enantiomer. However, differences in permeation rates between enantiomers and their racemates do not have to be related to stereoselective interactions, since they may also be explained by differences in physicochemical properties. The study also showed that there was no difference in the permeation enhancement ability between the (R)-(-) and (S)-(+) isomers of 6-aminohexanoic acid 2-octylester (the ERs were 2.72+/-0.42 and 2.79+/-0.60 for (R) and (S) enantiomers, respectively), suggesting that the enhancing properties of the compounds are not dependent on their spatial arrangement. Although stereoselective interactions between an enhancer and stratum corneum components may exist, they seem not to be important for the enhancer action.
Keywords: senioři; Aminocaproates; Analysis of Variance; Stereoisomerism; Theophylline; mužské pohlaví; Caproates; analýza rozptylu; stereoizomerie; ženské pohlaví; Humans; Skin; aminokapronáty; permeabilita; Permeability; kůže; Female; Aged; kapronáty; theofylin; lidé; Male